2006
DOI: 10.1073/pnas.0601676103
|View full text |Cite
|
Sign up to set email alerts
|

Histone chaperone Asf1 is required for histone H3 lysine 56 acetylation, a modification associated with S phase in mitosis and meiosis

Abstract: Histone acetylation affects many nuclear processes including transcription, chromatin assembly, and DNA damage repair. Acetylation of histone H3 lysine 56 (H3 K56ac) in budding yeast occurs during mitotic S phase and persists during DNA damage repair. Here, we show that H3 K56ac is also present during premeiotic S phase and is conserved in fission yeast. Furthermore, the H3 K56ac modification is not observed in the absence of the histone chaperone Asf1. asf1⌬ and H3 K56R mutants exhibit similar sensitivity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
271
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(292 citation statements)
references
References 32 publications
19
271
2
Order By: Relevance
“…S. cerevisiae mutants lacking Rtt109 or Asf1 display delayed cell-cycle progression (15), spontaneous DNA damage (5,17,18), unstable replication forks, and are extremely sensitive to DNA-damaging agents (8). In accordance, point mutation of H3 lysine 56 to arginine, which cannot be acetylated and mimics a positively charged, unacetylated lysine, results in similar phenotypes (5,14). Therefore, acetylation of H3K56 is a particularly important PTM for fungal growth.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…S. cerevisiae mutants lacking Rtt109 or Asf1 display delayed cell-cycle progression (15), spontaneous DNA damage (5,17,18), unstable replication forks, and are extremely sensitive to DNA-damaging agents (8). In accordance, point mutation of H3 lysine 56 to arginine, which cannot be acetylated and mimics a positively charged, unacetylated lysine, results in similar phenotypes (5,14). Therefore, acetylation of H3K56 is a particularly important PTM for fungal growth.…”
mentioning
confidence: 71%
“…In S. cerevisiae, H3K56 acetylation is required for replication fork stability (8,9), reassembly of chromatin after DNA damage repair, and histone association with chromatin assembly proteins (10)(11)(12)(13). A fungalspecific histone acetyl-transferase (HAT) enzyme, termed Rtt109, and its stimulatory histone chaperone cofactor, Asf1, are required for H3K56 acetylation (8,(14)(15)(16). S. cerevisiae mutants lacking Rtt109 or Asf1 display delayed cell-cycle progression (15), spontaneous DNA damage (5,17,18), unstable replication forks, and are extremely sensitive to DNA-damaging agents (8).…”
mentioning
confidence: 99%
“…This modification is predicted to allow a looser interaction of the histones with DNA, suggesting that it may contribute to chromatin assembly (15,16). Interestingly, recent work has indicated that deletion of the gene encoding the histone chaperone Asf1 greatly reduces the levels of acetylation of H3 on lysine 56 (17,18). Similarly, our previous work had found that yeast lacking the histone chaperone Asf1 has greatly reduced levels of acetylation on lysine 9 of histone H3 (19).…”
mentioning
confidence: 97%
“…In human cells, it is proposed that Asf1 can disrupt parental nucleosomes (Groth et al, 2007). Furthermore, Asf1 is required for acetylation of histone H3 lysine 56 (H3K56Ac), a mark of newly-synthesized histones that has been found to be important for DNA replication and DNA repair (Recht et al, 2006;Chen et al, 2008;Li et al, 2008).…”
Section: The Function Of Three Histone Chaperones In Rc Nucleosome Asmentioning
confidence: 99%